Magneto Hydro Dynamic two fluid flow of blood through stenosed artery - kumar, Surendra (JOURNAL OF ADVANCES IN MATHEMATICS, 2016)
When blood flow through artery, the two-phase nature of blood as a suspension becomes important as the diameter of the red blood cell (RBC) becomes comparable to the tube diameter. The aim of the present study is to analyzed the effect of magnetic field on the plug flow region, shear stress in the core and plasma layer in two-fluid flow of blood through stenosed artery. Besides magnetic field, the effect of Womersley parameter, thickness of stenosis and width of plasma layer are also discussed. Generated data are analyzed and discussed through graphs.